Comparative evaluation of sequential and premixed administration of hyperbaric bupivacaine with fentanyl in subarachnoid block for lower limb surgeries – A randomized prospective study - Vikram M Shivappagoudar; Jaya Subbu N; Bindu George; Karthik Jain M (Asian Journal of Medical Sciences, 2024)
Background: Subarachnoid block is the most commonly used anesthetic technique for lower limb surgeries. Fentanyl is very often combined with hyperbaric bupivacaine as an adjuvant. This study was conducted to compare the block characteristics by administrating bupivacaine and fentanyl in a sequential and premixed manner. Aims and Objectives: The primary objective was to compare the effects of hyperbaric bupivacaine and fentanyl administered either as a premixed solution or sequentially on block characteristics-onset of sensory and motor blockade, regression of block and duration of analgesia. The secondary objective was to study the hemodynamic changes and adverse effects. Materials and Methods: A total of 72 patients scheduled to undergo lower limb surgery were allocated to three groups. Patients in Group A received 15 mg of 0.5 % bupivacaine heavy (H), followed by 25 mcg of fentanyl intrathecally using different syringes. Group B received 25 mcg of fentanyl, followed by 15 mg of 0.5% bupivacaine H in a separate syringe. Group C received premixed 0.5 % bupivacaine H 15 mg and fentanyl 25 mcg in single syringe. The block characteristics-onset and regression of sensory and motor blockade, duration of analgesia, and adverse effects were studied. Results: The mean time (minutes) taken for onset of sensory block was 2.40±0.51 in group A, 4.80±0.53 in Group B and 6.70±0.50 in Group C. Mean time (minutes) taken for onset of motor block was 4.35±0.43 in Group A, while it was 5.64±0.65 and 7.32±0.64 in Groups B and C, respectively. Two segment regression and duration of motor blockade were found to be longer in Group A. Conclusion: Sequential intrathecal administration of bupivacaine followed by fentanyl has a faster onset and prolonged duration of block when compared to the premixed group.